ディガンマ関数の漸化式・正整数値・半正整数値

(1)漸化式

\[ \psi(z+1)=\psi(z)+\frac{1}{z} \]

(2)

\[ \psi(1)=-\gamma \]

(3)正整数値

\(n\in\mathbb{N}\)のとき、

\[ \psi(n)=H_{n-1}-\gamma \]

(4)

\[ \psi\left(\frac{1}{2}\right)=-\gamma-2\log2 \]

(5)半正整数値

\(n\in\mathbb{N}\)のとき、

\[ \psi\left(n-\frac{1}{2}\right)=H_{n-1}-2\sum_{j=1}^{2n-2}\frac{(-1)^{j}}{j}-\gamma-2\log2 \]

(1)

\begin{align*} \psi\left(z+1\right) & =\frac{d}{d\left(z+1\right)}\log\Gamma\left(z+1\right)\\ & =\frac{dz}{d\left(z+1\right)}\frac{d}{dz}\log\left(z\Gamma\left(z\right)\right)\\ & =\frac{d}{dz}\left(\log z+\log\Gamma\left(z\right)\right)\\ & =\frac{1}{z}+\psi\left(z\right) \end{align*}

(1)-2

\begin{align*} \psi(z+1) & =\lim_{n\rightarrow\infty}\left(\log n-\sum_{k=0}^{n}\frac{1}{z+1+k}\right)\\ & =\lim_{n\rightarrow\infty}\left(\log n-\sum_{k=1}^{n}\frac{1}{z+k}\right)\\ & =\lim_{n\rightarrow\infty}\left(\log n-\sum_{k=0}^{n}\frac{1}{z+k}\right)+\frac{1}{z}\\ & =\psi(z)+\frac{1}{z} \end{align*}

(2)

\begin{align*} \psi(1) & =-\gamma-\sum_{k=0}^{\infty}\left(\frac{1}{1+k}-\frac{1}{k+1}\right)\\ & =-\gamma \end{align*}

(3)

\(m\in\mathbb{N}\)とする。
\begin{align*} \psi(m) & =\sum_{j=1}^{m-1}\left(\psi(j+1)-\psi(j)\right)+\psi(1)\\ & =\sum_{j=1}^{m-1}\frac{1}{j}+\psi(1)\\ & =H_{m-1}-\gamma \end{align*}

(4)

\begin{align*} \psi\left(\frac{1}{2}\right) & =-\gamma-\lim_{n\rightarrow\infty}\sum_{k=0}^{n}\left(\frac{1}{\frac{1}{2}+k}-\frac{1}{k+1}\right)\\ & =-\gamma-\lim_{n\rightarrow\infty}\sum_{k=0}^{n}\left(\frac{2}{1+2k}-\frac{1}{k+1}\right)\\ & =-\gamma-2\lim_{n\rightarrow\infty}\sum_{k=0}^{n}\left(\frac{1}{1+2k}-\frac{1}{2(k+1)}\right)\\ & =-\gamma-2\lim_{n\rightarrow\infty}\sum_{k=0}^{n}\left(\frac{(-1)^{2k+1+1}}{2k+1}+\frac{(-1)^{2(k+1)+1}}{2(k+1)}\right)\\ & =-\gamma-2\lim_{n\rightarrow\infty}\sum_{k=1}^{2n+2}\left(\frac{(-1)^{k+1}}{k}\right)\\ & =-\gamma-2\log2 \end{align*}

(5)

\(n\in\mathbb{N}\)のとき、

\begin{align*} \psi\left(m-\frac{1}{2}\right) & =\sum_{j=0}^{m-2}\left(\psi\left(j+1+\frac{1}{2}\right)-\psi\left(j+\frac{1}{2}\right)\right)+\psi(\frac{1}{2})\\ & =\sum_{j=0}^{m-2}\frac{1}{j+\frac{1}{2}}+\psi\left(\frac{1}{2}\right)\\ & =2\sum_{j=0}^{m-2}\frac{1}{2j+1}+\psi\left(\frac{1}{2}\right)\\ & =2\left(\sum_{j=1}^{2m-2}\frac{1}{j}-\sum_{j=1}^{m-1}\frac{1}{2j}\right)+\psi\left(\frac{1}{2}\right)\\ & =2\left(\sum_{j=1}^{m-1}\frac{1}{2j}+\sum_{j=1}^{m-1}\frac{1}{2j-1}-\sum_{j=1}^{m-1}\frac{1}{2j}\right)+\psi\left(\frac{1}{2}\right)\\ & =H_{m-1}-2\sum_{j=1}^{2m-2}\frac{(-1)^{j}}{j}-\gamma-2\log2 \end{align*}

ページ情報

タイトル

ディガンマ関数の漸化式・正整数値・半正整数値

URL

https://www.nomuramath.com/euj5e7c7/

SNSボタン